Compartilhamento do conhecimento e confiança organizacional em ambientes fortemente hierarquizados - Rêgo, Reinaldo Costa de Almeida (2012)
Knowledge sharing and organizational trust are factors of great interest in research on knowledge management. This thesis aims to identify how organizational trust influences the sharing knowledge propensity in strong hierarchical structures, studying the effects of career satisfaction, organizational commitment and time of exposure to hierarchy in this process. The hypothetical-deductive method, applied with the structural equation models technique to a sample of 655 military professionals of the Brazilian Army resulted in the mediation of affective organizational commitment in the relationship between organizational trust and knowledge sharing propensity. The results also suggest that perceived receipt of useful knowledge and marital status are significant variables to explain the variance of the knowledge sharing propensity. Finally, the time of exposure to hierarchy directly impacts the studied variables, however, do not interfere in the relationship between the organizational commitment and the propensity of knowledge sharing. The results of this thesis contribute to a better understanding the knowledge sharing phenomenon in the organizational environment.